First Experience With The GoBack-Catheter For Successful Crossing of Complex Chronic Total Occlusions in Lower Limb Arteries. (October 2022) - Bakker, Olaf; Bausback, Yvonne; Wittig, Tim; Branzan, Daniela; Steiner, Sabine; Fischer, Axel; Konert, Manuela; Düsing, Sandra; Banning-Eichenseer, Ursula; Scheinert, Dierk; Schmidt, Andrej
Purpose: To evaluate the use of the GoBack-catheter (Upstream Peripheral Technologies) in complex revascularizations in lower limb arteries. Materials and Methods: In this retrospective single-center study, the results of the first 100 consecutive patients including 101 limb-revascularizations, performed between May 2018 and July 2020 with the study device, were analyzed. In all cases, guidewire-crossing failed, and all lesions were chronic total occlusions (CTO), either de novo, reocclusions, or in-stent reocclusions. Successful crossing was defined as passing the CTO using the study device. Patency at discharge and after 30 days was defined as less than 50% restenosis on duplex sonography, without target lesion revascularization. Results: Median lesion length was 24 cm and 38 patients (37.6%) had a calcium grading according to the peripheral arterial calcium scoring system (PACSS) of 4 or 5. In 20.8% of patients, an occluded stent was treated. CTOs involved the femoropopliteal segment in 91.1%, iliac arteries in 5.9%, and tibial arteries in 7.9%. The GoBack-catheter was employed for entering into or crossing through parts or the full length of a CTO or an occluded stent as well as for re-entering into the true lumen after subintimal crossing. The device was used via contralateral and ipsilateral antegrade as well as retrograde access with an overall technical success rate of 92.1%. In 3 patients minor bleeding occurred at the crossing or re-entry site, which were managed conservatively. Thirty-day adverse limb events comprised minor amputations in 4 patients (4.0%), 1 major amputation (1.0%), and reocclusions in 7 limbs (6.9%). Conclusion: The new GoBack-catheter offers versatile endovascular applicability for complex CTO recanalization in a broad range of peripheral vascular interventions with a high technical success and low complication rate.